PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS KOMIK PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL KELAS IV MI NURUL HIDAYAH ROWOREJO NEGERIKATON PESAWARAN - HIDAYAH, NURUL (Universitas Islam Negeri Raden Intan Lampung, 2017)
The study was conducted with the aim of developing media-based learning cooperative comic material on the subjects of Social Sciences. Media-based learning comic created to facilitate teaching and learning activities for teachers and learners. With the comic-based learning media students more interested and motivated in learning activities. Research conducted by the author is research development by using models Borg and Gall performed with several stages of conducting research preliminary studies, product design and production development, valisadasi experts that due diligence based learning media comic that consists of three subject matter experts, three experts media and three teachers, field tests consist of a small group test with ten learners and test a large group of twenty-seven learners. This research was conducted in MI Nurul Hidayah Roworejo Negerikaton Pesawaran. Based on these stages, it can be concluded that the instructional media comics on the subjects of Social Sciences cooperative material obtained average value of materials experts at 165.91% categorized as very feasible, an average of 70.73% a decent media experts and average -rata votes 88.58% of teachers are very decent. While the assessment given by students at the stage of testing a small group, and large group test earned an average percentage of 83.67% were categorized as very feasible. and 99.07% were categorized as very feasible, this shows the comic-based learning media developed a very practical and fit for use in the learning process.Keywords: Media learning, comics, social science.